Femtosecond laser-induced transformation mechanism from 1D groove structure to 2D microholes structure on the surface of Zr-based metallic glasses. (February 2022) - Huang, Hanxuan; Zhang, Peilei; Yu, Zhishui; Shen, Lei; Shi, Haichuan; Tian, Yingtao
Highlights: Femtosecond laser induces LIPSS, SWPSS and microporous structure on Zr-based amorphous.. Compare the period, amplitude, surface fluctuation and roughness of different micro-nano structures. The effective energy density increases, LIPSS transitions to SWPSS, and finally into a self-organized microporous structure.. The micro-remelting caused by the heat accumulation effect is the key to the transformation of the micro-nano structure. The self-organized microholes structure has the great ability to reduce E. coli adhesion. Abstract: Laser induced micro-nano texture formation on the surface of solid materials has become a research hotspot in the field of material surface modification. However, due to its extremely easy crystallization characteristics, the study of laser-induced surface modification of bulk amorphous alloy lags behind. In this study, femtosecond laser was used to induce one-dimensional LIPSS (Laser-induced periodic surface structures), SWPSS (Super-wavelength periodic surface structure), a mixed state structure of LIPSS + SWPSS and two-dimensional self-organized microholes structure on surface of the Zr55Cu16Ni15Ti10Al4 bulk amorphous alloy. The numerical difference between LIPSS, SWPSS and self-organized microholes structure in different dimensions such as period, groove width, profile height, etc. were compared, and the roughness of different micro-nano textures and the size of surface undulations were evaluated. The effects of different process parameters on the formation and transformation of micro-nano texture on the surface of zirconium bulk amorphous alloys were investigated. The mechanism of the transformation from LIPSS to SWPSS and finally to two-dimensional self-organized microholes structure was analyzed in detail. Finally, Escherichia coli was cultured on the amorphous surface of Zr-based metallic glasses with different structure. To examine the effect of micro-nano texture on the antibacterial properties of Zr-based metallic glasses surfaces. It is found that the self-organized microholes structure has the best effect in reducing the adhesion of bacteria on the surface of the material.